Increasing Productivity in CPO Production Using The Objective Matrix Method - Irwansyah, Defi; Erliana, Cut Ita; Fadlisyah, Fadlisyah; Ula, Mutammimul; Fahrozi, Mahlil; Harun, Rofiq (International Journal of Engineering, Science and Information Technology, 2022)
PT. Ika Bina Agro Wisesa (IBAS) is a company that produces products in the form of crude oil or CPO (Crude Palm Oil). The company sets a minimum production target of FFB that must be processed to reach 30 tons in one boiling with a minimum production target of 600 tons/day. The company is required to increase productivity. The problem so far is that the company has never measured the productivity of the production process, which will then affect the achievement of production targets. Measurement of productivity is critical because the measursizeoductivity can determine whether the company meets productivity targets for production or not. Therefore, it is necessary to measure productivity to assess the value of productivity and efforts to increase productivity in CPO production and how to increase productivity in CPO production and efforts to increase productivity using the Objective Matrix (OMAX) method at PT. Ika Bina Agro Wisesa. Analysis of productivity using the OMAX method, ratio 3 (labor productivity) and ratio 4 (machine productivity) has a very high percentage of poor performance, which means that ratio and 4 have an insufficient level of productivity. Unlike the case with the achievement of productivity ratio 1 (productivity of raw materials) and ratio 2 (productivity of working hours) wh, ich shows a low percentage of poor performance, which means that the productivity level of ratio one and ratio 2 has a better productivity level than ratio three and ratio 4 Analysis The results of the productivity index in the company decreased and increased for each month, in November it experienced a decrease of -79.49, while in December it experienced a significant increase in the amount of 595.02 and January at 69.98. in February decreased to -23.63. Furthermore, productivity in March - September 2021 was unstable, with an increase and dropped for July, a decrease of -0.64 and, a slight increase in August of 0.28.